ORGANIZATION OF GAME ACTIVITIES IN PRACTICAL CLASSES ON GERMAN AS A SECOND LANGUAGE IN FACULTY STUDENT TRAINING SYSTEMS FOREIGN LANGUAGES FOR FOREIGN COMMUNICATION (Pedagogy of Higher and Secondary Education, 2007)
The article shows the essence of the students' playing activity during their foreign language communication training on the practical tasks by German. The author gives the examples of using some kinds of games in practice and demonstrates the effectiveness of using playing activities of students as prospective teachers in order to prepare them to foreign communication.